Effects of Glucagon like Peptide-1 agonists on patients with overactive bladder: A pilot study - Max D. Sandler; Adam D. Williams; Alan Wein; Katherine Amin; Raveen Syan (Continence Reports)
Purpose:: To explore preliminary data on the subjective impact of Glucagon-Like Peptide-1 (GLP-1) agonists, commonly used for diabetes and obesity, on symptoms of overactive bladder (OAB), in order to guide future, larger-scale investigations. Methods:: We distributed an anonymous survey on an online forum. Participants aged 18 or older who had used GLP-1 agonists and experienced OAB symptoms were eligible. We collected data on participants’ OAB symptoms, body weight changes, reasons for GLP-1 prescription, and demographics. Data was analyzed using SAS® software, with significance set at p < 0.05. Results:: Of 33 respondents, 27 identified as female and 6 male. All used semaglutide, primarily for weight loss (96.9%). Four had a urinary condition besides OAB. Eleven (33.3%) reported OAB symptom improvement after starting GLP-1 agonists with mean weight loss of 12.2%, but this was not significantly different from those with no change or worsening symptoms (8.4% and 10% mean weight loss, respectively; p = 0.24). Half of those with OAB episodes at least once daily experienced symptom improvement, compared to 7.7% with less frequent symptoms (p = 0.01). Of participants reporting symptom improvement, 90.91% experienced OAB daily (p = 0.01). Conclusion:: While weight loss can improve OAB symptoms, the impact of GLP-1 agonists remains unclear. Our findings may suggest that those with more frequent OAB symptoms at baseline may derive greater benefit from GLP-1 agonists, offering a potential hypothesis for future investigation. Further studies are needed to explore how these medications impact management of OAB.